2018
DOI: 10.1021/acs.jproteome.8b00497
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Multifaceted Information to Predict Mycobacterium tuberculosis-Human Protein-Protein Interactions

Abstract: Tuberculosis (TB) is one of the biggest infectious disease killers caused by Mycobacterium tuberculosis (MTB). Studying the protein-protein interactions (PPIs) between MTB and human can deepen our understanding of the pathogenesis of TB and offer new clues to the treatment against MTB infection, but the experimentally validated interactions are especially scarce in this regard. Herein we proposed an integrated framework that combined template-, domain-domain interaction-, and machine learning-based methods to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…The resulting PPI networks often have confidence scores for putative interactions that allow thresholding and the use of network analysis algorithms that utilize these scores ( 112 ). Microbial PPI prediction has been carried out using several algorithms including random forests ( 113 117 ), support vector machines ( 118 120 ), and Bayesian classifiers ( 121 123 ). A related method is probabilistic functional integrated networks (PFINs), which combine multiple data types in a probabilistic framework to produce a network of confidence-weighted interactions ( 124 126 ).…”
Section: Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting PPI networks often have confidence scores for putative interactions that allow thresholding and the use of network analysis algorithms that utilize these scores ( 112 ). Microbial PPI prediction has been carried out using several algorithms including random forests ( 113 117 ), support vector machines ( 118 120 ), and Bayesian classifiers ( 121 123 ). A related method is probabilistic functional integrated networks (PFINs), which combine multiple data types in a probabilistic framework to produce a network of confidence-weighted interactions ( 124 126 ).…”
Section: Machine Learningmentioning
confidence: 99%
“…A DDI-based network suggested that human– M. tuberculosis PPIs tend to have more domains than intraspecies interactions ( 138 ), and this trend was later observed in an interolog-based mapping study, which also revealed that hub proteins of intraspecies networks tend to be involved in host–pathogen PPI ( 148 ). Using a random forest framework, the cancer pathway was involved in M. tuberculosis infection ( 117 ), while a DDI network implicated several PPIs involving heat shock, redox proteins ( 224 ). Finally, a combination of interolog and DDI mapping associated several genes of the host immune responses to M. tuberculosis infection ( 65 ).…”
Section: Pathogen–host Interactionsmentioning
confidence: 99%
“…Tuberculosis (TB), a major chronic infectious disease of the lungs caused by Mycobacterium tuberculosis , has become a top killer among infectious diseases due to an epidemic of coinfections and drug resistance ( 1 , 2 ). According to the World Health Organization’s “Global tuberculosis report 2020,” in 2019, there were approximately two billion individuals infected with M. tuberculosis worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of Mtb persistence mediators have been studied e.g. ( Wang et al., 2010 ; Huo et al., 2015 ; Sun et al., 2018 ), structural information is still lacking, particularly for those that form large assemblies. In fact, most protein interactions have only been detected indirectly and there is poor correlation between different detection methods ( Mackay et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%